Temporal change in inflammatory biomarkers and risk of cardiovascular events: the Multi‐ethnic Study of Atherosclerosis. (9th July 2021) - Shabani, Mahsima; Bakhshi, Hooman; Ostovaneh, Mohammad R.; Ma, Xiaoyang; Wu, Colin O.; Ambale‐Venkatesh, Bharath; Blaha, Michael J.; Allison, Matthew A.; Budoff, Matthew J.; Cushman, Mary; Tracy, Russell P.; Herrington, David M.; et al.
Abstract: Aims: Little is known about the association of temporal changes in inflammatory biomarkers and the risk of death and cardiovascular diseases. We aimed to evaluate the association between temporal changes in C‐reactive protein (CRP), fibrinogen, and interleukin‐6 (IL‐6) and risk of heart failure (HF), cardiovascular disease (CVD), and all‐cause mortality in individuals without a history of prior CVD. Methods and results: Participants from the Multi‐Ethnic Study of Atherosclerosis (MESA) cohort with repeated measures of inflammatory biomarkers and no CVD event prior to the second measure were included. Quantitative measures, annual change, and biomarker change categories were used as main predictors in Cox proportional hazard models stratified based on sex and statin use. A total of 2258 subjects (50.6% female, mean age of 62 years) were studied over an average of 8.1 years of follow‐up. The median annual decrease in CRP levels was 0.08 mg/L. Fibrinogen and IL‐6 levels increased by a median of 30 mg/dL and 0.24 pg/mL annually. Temporal changes in CRP were positively associated with HF risk among females (HR: 1.18 per each standard deviation increase, P < 0.001) and other CVD in both female (HR: 1.12, P = 0.004) and male participants (HR: 1.24, P = 0.003). The association of CRP change with HF and other CVD was consistently observed in statin users (HR: 1.23 per SD increase, P = 0.001 for HF and HR: 1.19 per SD increase, P < 0.001 for other CVD). There were no significant associations between temporal changes of fibrinogen or IL‐6 with HF or other CVD. Men with sustained high values of IL‐6 had a 2.3‐fold higher risk of all‐cause mortality ( P < 0.001) compared with those with sustained low values. Conclusions: Temporal change in CRP is associated with HF only in women and statin users, and other CVD in both women and men, and statin users. Annual changes in fibrinogen and IL‐6 were not predictive of cardiovascular outcomes in either sex.